Sowing Uncertainty: What We Do and Don't Know about the Planting of Pesticide-Treated Seed. (18th March 2020) - Hitaj, Claudia; Smith, David J; Code, Aimee; Wechsler, Seth; Esker, Paul D; Douglas, Margaret R
ABSTRACT: Farmers, regulators, and researchers rely on pesticide use data to assess the effects of pesticides on crop yield, farm economics, off-target organisms, and human health. The publicly available pesticide use data in the United States do not currently account for pesticides applied as seed treatments. We find that seed treatment use has increased in major field crops over the last several decades but that there is a high degree of uncertainty about the extent of acreage planted with treated seeds, the amount of regional variability, and the use of certain active ingredients. One reason for this uncertainty is that farmers are less likely to know what pesticides are on their seed than they are about what pesticides are applied conventionally to their crops. This lack of information affects the quality and availability of seed treatment data and also farmers' ability to tailor pesticide use to production and environmental goals.